Mystic regimes : Sufism and the state in Iran, from the late Qajar era to the Islamic Republic - Bos, Matthijs van den (Social, economic, and political studies of the Middle East and Asia, 2002)
This work is a socio-scientific and Iranological study of two Iranian, Sh'ite Sufi orders in the 20th century. It studies their comparative social development in relation to political regimes and explores the cultural repertoires that Sufis have used to cope with these.